Therapeutic effects of progesterone in animal models of neurological disorders - de Nicola, Alejandro Federico (2013)
Substantial evidence supports that progesterone exerts many functions in the central and peripheral nervous system unrelated to its classical role in reproduction. In this review we first discussed progesterone effects following binding to the classical intracellular progesterone receptors A and B and several forms of membrane progesterone receptors, the modulation of intracellular signalling cascades and the interaction of progesterone reduced metabolites with neurotransmitter receptors. We next described our results involving animal models of human neuropathologies to elucidate the protective roles of progesterone. We described: (a) the protective and promyelinating effects of progesterone in experimental spinal cord injury; (b) the progesterone protective effects exerted upon motoneurons in the degenerating spinal cord of Wobbler mouse model of amyotropic lateral sclerosis; (c) the protective and anti-inflammatory effects of progesterone in the murine experimental autoimmune encephalomyelitis model of multiple sclerosis and after lysolecithin demyelination; (d) the progesterone prevention of nociception and neuropathic pain which follow spinal cord injury; and (e) the protective effect of progesterone in experimental ischemic stroke. Whenever available, the molecular mechanisms involved in these progesterone effects were examined. The multiplicity of progesterone beneficial effects has opened new venues of research for neurological disorders. In this way, results obtained in animal models could provide the basis for novel therapeutic strategies and pre-clinical studies.